(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
While the rate of entrepreneurship has continued to rise in Nigeria, the development of enterprises has remained below expectation, especially in the state in question, Osun State, where entrepreneurial activities have the potential to boost the economy. This research examines the effects of financial incentives on the development of startups. Data in this study were collected through a cross-sectional survey design. The target population are start-up entrepreneurs or newly launched businesses recorded within the last 3 years in these sectors: technology, manufacturing, agriculture, healthcare and retail operating in Osun state which is infinite with a sample size of 385 respondent and participants were identified through a snowball sampling technique. The observed data from the respondents was analyzed using descriptive and inferential statistics. Regression analysis was used to test the hypotheses. Data was analyzed using a statistical package for social science (SPSS) 27. The result revealed positive relationship among individual contributions of the predictors (financial incentive, training program, regulatory environment) to the dependent variable (startup development) with unstandardized coefficient (B = 1.405) which predicts the value of the dependent variable (startup development) when all predictors are zero and T-value (5.452) and Sig. (.000). The research therefore recommended that entrepreneurship development agencies should be imparting practical and industry-specific training programs.